Artificial neural network data fusion-mediated dual-mode sensor based on Fe3O4@PdIr for Salmonella typhimurium detection in food - Mengxia Duan; Wenxiu Zheng; Zepeng Gu; Man Ding; Shiping Luo; Zhouping Wang; Shijia Wu; Yukun Huang; Nuo Duan (Food Research International, 2026)

Formulation-resolved VOC emission factors measured in a dynamic chamber and corresponding secondary formation potentials for selected architectural paints - Fanglin Wang; Ka Hei Lui; Donger Lai; Guoyang Lei; Chung Ling Man; Yansu He; Dasa Gu; Zhe Wang; Man Nin Chan; Donald R. Blake; Kin Fai Ho (Environmental Pollution, 2026)

Non-destructive in situ methanol sensing in Li-ion battery electrolytes via an embedded organic electrochemical transistor with non-traditional configuration - Ziyang Niu; Jianguo Lu; Xiangyi Bai; Shu Nie; Yi Zhu; Xiuquan Gu; Dusong Hou; Li Meng; Man-Kay Law; Sheng Huang (Chemical Engineering Journal, 2026)

Allelic variation in cis-regulation of UNE12 underlies differential Verticillium wilt resistance in tetraploid cottons - Meixia Xie; Ziming Li; Jiaxuan Zhao; Minghui Ye; Mengjia Jiao; Zhicheng Wang; Xinxin Zheng; Xinyu Zhang; Jin Zhang; Yan Wang; Man Gu; Lingxia Zhai; et al. (Science Bulletin, 2026)

Lactococcus cremoris subsp. sagaensis subsp. nov., Isolated from Naturally Fermented Yogurt - Lin Cheng; Tian-Xue Wang; Chun Yan Li; Chaoxin Man; Chun Tao Gu (Current Microbiology, 2026)

New ecdysteroids with anticomplementary activity from roots of Leuzea uniflora (L.) holub - Wen-qing Du; Can Liu; Ruo-mei Li; Ning-ning Shi; Yan-nan Ji; Jin-long Qi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Laser-induced hybrid interphase for corrosion dispersion toward durable metal–polymer interfaces in marine environment - Shuangshuang Li; Man Gu; Hailang Wan; Jianping Lin (Chemical Engineering Journal, 2026)

Polystyrene nanoplastic-encapsulated extracellular vesicles promote blood–brain barrier breakdown and accumulate in the brain - Min Jae Kim; Hyun Seung Shin; Yun Hee So; Dong Hun Lee; Jae-Eon Lee; Hyeon-Gu Kang; DongJoo Joung; Eui-Man Jung; Beum-Soo An (Journal of Hazardous Materials, 2026)

Lacticaseibacillus boliensis sp. nov., Isolated from Traditional Chinese Pickle - Jing-Hao Wang; Si-Tong Song; Chaoxin Man; Chun Tao Gu (Current Microbiology, 2026)

Structural evolution-based ancestral sequence reconstruction of medium-chain alcohol dehydrogenase for efficient synthesis of fused-ring chiral alcohols - Jun Wang; Songyin Zhao; Lehang Li; Manman Zhu; Man Zou; Xin Su; Jie Gu; Yan Xu; Yao Nie (Bioresource Technology, 2026)

New nor-tirucallane triterpenoid with antitumor activity from Ailanthus altissima (mill.) swingle - Can Liu; Jun-ling Guo; Shuo-yu Zhao; Ning-ning Shi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Body size drives male reproductive success through nest competition and paternal care in the toad Leptobrachium boringii - Raziya Abliz; Wei Zhang; Shuang Liu; Rufeng Xiong; Chunhua Huang; Jun Li; Mian Zhao; Zhirong Gu; Man Su; Wei Liu; Hua Wu (Animal Behaviour, 2026)

Overlooked role of soil microbial-derived carbon in promoting neurotoxic methylmercury production - Man Yang; Zhi-Cheng Hu; Hui-Wen Liu; Wen Zhang; Yun-Yun Hao; Qin Liu; Jia-Xuan Meng; Bo Meng; Qiaoyun Huang; Baohua Gu; Yu-Rong Liu (Journal of Hazardous Materials, 2026)

Unravelling methylmercury formation in high-altitude Tibetan thermokarst lakes - Xia Lu; Xiaosha Liu; Zhixia Yang; Liang Li; Man Yang; Yu-Rong Liu; Baohua Gu; Cuicui Mu (Journal of Hazardous Materials, 2026)

What drives energy conservation in Zhejiang households? Quantifying economic dominance, policy, and social moderators in a TPB-KAP integrated framework - Jiasheng Li; Zhipan Gu; Zishan Zhu; Yi Xiang; Shan Man; Hongyao Chen; Yiming Zhang; Bo Chen; Meng Du (Energy and Buildings, 2026)

Tassel counting of individual ridge from UAV RGB imagery based on YOLOv8m with deep SORT and double-step Otsu thresholding algorithm by filtering abnormal IDs for maize breeding - Man Xia; Leilei He; Yu Gu; Xiaojuan Liu; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Yan Long; Anastasia Grecheneva; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Long-term effects of the hydrophilic and electrophilic modified magnetic carriers on partial nitrification at low temperatures: Enhancing nitrite supply by stimulating major enzyme gene expression - Fang Man; Yi Xue; Yuexin Yu; Chengyu Gu; Sijia Ma; Yuan Lin; Hongqiang Ren; Ke Xu (Environmental Research, 2025)

Silencing aquaporin 1 inhibits autophagy to exert anti-rheumatoid arthritis effects in TNF-α-induced fibroblast-like synoviocytes and adjuvant-induced arthritis rats - Man-yu Zhang; Meng-qing Wang; Yan Huang; Sheng-long Gu; Meng-yuan Zhou; Ze-shan Xu; Ling-ling Li; Min Lv; Li Cai; Rong Li (Inflammation Research, 2025)

Multifunctional textiles with bimetallic MOFs for enhanced ammonia uptake and protective applications - Yajie Shu; Zimeng Sheng; Danni Wang; Hao Gu; Yumeng Tang; Guangsheng Zhu; Man Zhang; Jinfeng Wang; Jinming Zhang; Haibao Huang (Chemical Engineering Journal, 2025)

Online detection of broken and impurity rates in half-feed peanut combine harvesters based on improved YOLOv8-Seg - Man Gu; Haiyang Shen; Jie Ling; Zhaoyang Yu; Weiwen Luo; Feng Wu; Fengwei Gu; Zhichao Hu (Computers and Electronics in Agriculture, 2025)

Pathway to carbon neutrality in the iron and steel industry of China: a LEAP-China-IS model assessment - Yueqing Gu; Chongchao Pan; Wenjie Liu; Zeyi Jiang; Man Huang; Wenchao Wang (Environmental Pollution, 2025)

Centennial-scale evolution, source apportionment, and ecological risks of heavy metals in Daya Bay, South China sea - Xiangtian Man; Jian Sun; Yu Xiang; Hong Su; Honghui Huang; Yangguang Gu; Han Zhang; Richard W. Jordan; Shijun Jiang (Environmental Pollution, 2025)

Improving dynamical downscaling simulations of western North Pacific tropical cyclones using bias-corrected CMIP6 data - Ying Han; Zhongfeng Xu; Meng-Zhuo Zhang; Chi-Yung Tam; Vincent S. Cheng; Hon-man Wong; Xiaofeng He; Yi Wang; Si-nan Gu (Climate Dynamics, 2025)

Algae biofilm produces less microbe-derived dissolved organic nitrogen under higher C/N ratio conditions - Yuexin Yu; Yuan Lin; Chengyu Gu; Fang Man; Sijia Ma; Yi Xue; Hongqiang Ren; Ke Xu (Environmental Research, 2025)

Electrical Detection of Shale Gas Layers Based on Wide-Field Electromagnetic Method - Li-Xin Man; Zhang-Kun Tan; Jian-Chao Jia; Zhi-Wen Gu; Chang-Heng Yu; Xue-Bo Yin (Applied Geophysics, 2025)

Alveolar surfactant-mimicking inhaled biomimetic nanovaccine with alveolar macrophage-targeting property potentiates anti-mpox immunity - Bin Li; Jiamei Wang; Judun Zheng; Wei Wang; Lingjie He; Yan Yan; Xinting Fu; Xingjie You; Man Gu; Han Duan; Yue Jia; Qin Gu; et al. (Chemical Engineering Journal, 2025)

Deciphering the role of extracellular polymeric substances in the adsorption of perfluorooctanoic acid during sludge alkaline fermentation: Experimental study and molecular dynamics simulation - Chengyu Gu; Sijia Ma; Fang Man; Yuexin Yu; Yuan Lin; Yi Xue; Yanru Wang; Hongqiang Ren; Ke Xu (Chemical Engineering Journal, 2025)

A multi-objective path planning method for ships based on constrained policy optimization - Man Zhu; Mian Kong; Yuanqiao Wen; Shangding Gu; Bai Xue; Tao Huang (Ocean Engineering, 2025)

Dual functional Zn doped chitosan fibers restrain the challenge of anode and cathode in lithium-sulfur batteries - Dong Wang; Xianrui Bai; Jianzong Man; Hua Yang; Gaohui Du; Zhaoyang Wang; Pengfang Zhang; Lingyang Liu; Yu Gu (Chemical Engineering Journal, 2025)

Combined Effects of Cadmium and Lead on Growth Performance and Kidney Function in Broiler Chicken - Man Zhao; Longqiang Xie; Wenbin Huang; Meiling Li; Xin Gu; Wei Zhang; Jintao Wei; Niya Zhang (Biological Trace Element Research, 2025)

The mechanism of selective separation of stibnite and arsenopyrite by Cu2+ coordination assembly KBX collector - Man Chen; Jing Zhong Kuang; Zheyu Huang; Yusufujiang Mubula; Yuting Guo; Hongju Gu; Tingsheng Qiu (Minerals Engineering, 2024)

Identification of major histocompatibility complex II gene in Pampus argenteus and the expression pattern in Pampus argenteus kidney cell line under the pathogen stress - Youyi Zhang; Jiabao Hu; Yuanbo Li; Weiwei Gu; Zukang Feng; Kaiheng Yan; Man Zhang; Yaya Li; Zi Yuan; Xiaomei Sun; Lu Zhang; Shanliang Xu; et al. (Aquaculture, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

Impact of Dietary Cadmium Intake from Rice on Renal Function Biomarker and Population Toxicokinetic Modelling - Yi Gu; Jun Man; Liqin Su; Shengnan Zhang; Fang-Jie Zhao; Yijun Yao; Peng Wang (Exposure and Health, 2024)

Simulated cold spell: Changes of lipid metabolism on silver pomfret during cooling and rewarming - Man Zhang; Jiabao Hu; Jiajie Zhu; Mengke Tang; Youyi Zhang; Yaya Li; Weiwei Gu; Huan Jiang; Danli Wang; Shanliang Xu; Xiaojun Yan; Yajun Wang (Aquaculture, 2024)

Tenascin can inhibit apoptosis induced by copper in silver pomfret (Pampus argenteus) - Jiabao Hu; Youyi Zhang; Yuanbo Li; Weiwei Gu; Zukang Feng; Kaiheng Yan; Man Zhang; Yaya Li; Rongyue Zheng; Shanliang Xu; Yajun Wang; Xiaojun Yan (Aquaculture, 2024)

Digitalization to achieve greener healthcare supply chain - Lo Cham Man; Yong Lin; Gu Pang; Joseph Sanderson; Keru Duan (Journal of Cleaner Production, 2024)

The mediation mechanism of calcium ions on black bean type 3 resistant starch: Metabolomics, structure characteristics and digestibility - Qingyu Yang; Xiling Zhang; Chenqi Gu; Man Li; Xiufa Hu; Yuzhe Gao; Zhongman Min; Weijia Zhang; Weijie Wu (Food Chemistry, 2024)

Spatial Distribution, Risk Assessment, Source Apportionment and Stabilization Performance of Potentially Toxic Elements in Sediments of Dongdagou River, Northwest China - Duan Zhao; Yimin Sang; Qian Zhang; Yang Man; Yanhe Han; Bin Wu; Caiyun Guo; Qingbao Gu (Water, Air, & Soil Pollution, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Evaluation of benefits and risks of immunosuppressive drugs in biomaterial-based neural progenitor cell transplantation for spinal cord injury repair - Bo Guo; Xinhao Zhao; Yunlong Zou; Xiaokang Cheng; Zheng Sun; Xiaoyu Xue; Man Yin; Chen Jin; Zhenni Chen; Rui Quan; Wenbin Liu; Bin Chen; et al. (Chemical Engineering Journal, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Enhanced fatty acid storage combined with the multi-factor optimization of fermentation for high-level production of docosahexaenoic acid in Schizochytrium sp. - Yu-Lei Jia; Ying Zhang; Lu-Wei Xu; Zi-Xu Zhang; Ying-Shuang Xu; Wang Ma; Yang Gu; Xiao-Man Sun (Bioresource Technology, 2024)

Immune strategies of silver pomfret (Pampus argenteus) infected with Nocardia seriolae at different infection stages - Youyi Zhang; Jiabao Hu; Yuanbo Li; Feirong Yuan; Kaiheng Yan; Weiwei Gu; Man Zhang; Yaya Li; Xiang Huang; Cheng Zhang; Dingyuan Zhang; Shanliang Xu; et al. (Aquaculture, 2024)

Effect of light intensity on the accumulation of protostane triterpenes in Asian water plantain (Alisma orientale) - Wenqing Wu; Simeng Li; Wei Gu; Rong Tian; Man Luo; Junjie Tang; Min Tang; Yinzhi Wu (Acta Physiologiae Plantarum, 2024)

Testate amoebae (Protozoa) in lakes of the Qinghai-Tibet Plateau: Biodiversity, community structures, and protozoic biosilicification in relation to environmental properties and climate warming - Yangmin Qin; Anatoly Bobrov; Daniel Puppe; Hui Li; Baiying Man; Jing Gong; Jie Wang; Yongde Cui; Yansheng Gu; Ulrike Herzschuh; Shucheng Xie (Science of The Total Environment, 2024)

Quasi-closed-loop approach for facile and environmentally friendly red mud reutilization as advanced Li-ion anode material - Dawei Lan; Yixun Gu; Xianglong Chen; Man Mo; Zhijie Fang; Panyu Xiong; Weichi Ye; Gangli Zhao; Tianshi Xiong; Minfeng Huang; Weijian Li; Haiqing Zhan; et al. (Journal of Cleaner Production, 2024)

Distribution of microplastic contamination in the major tributaries of the Yellow River on the Loess Plateau - Xiaoli Zhao; Minmin Qiang; Yuan Yuan; Man Zhang; Wenjing Wu; Jiaocheng Zhang; Zesen Gao; Xinmei Gu; Sitian Ma; Zihan Liu; Lu Cai; Jianqiao Han (Science of The Total Environment, 2023)

A highly sensitive sandwich-type electrochemical aptasensor using a pair of novel truncated aptamers for the detection of vaspin - Eun Ryung Kim; Thi Thanh-Thao Dang; Su Jin Lee; Thi Thanh-Qui Nguyen; Jee-Woong Park; Man Bock Gu (Chemical Engineering Journal, 2023)

Mechanism of Coal Permeability Enhancement by a Series of Mechanically Over-excavated Cavities Along Drainage Boreholes - Chun Liu; Zhongyi Man; Fubao Zhou; Jiaxing Gu; Mingyao Wei; YongLong Wang (Rock Mechanics and Rock Engineering, 2023)

Change and Regulation of Nutritional Metabolism in Silver Pomfret During Compensatory Growth - Jiabao Hu; Youyi Zhang; Kaiheng Yan; Man Zhang; Yaya Li; Yuanbo Li; Weiwei Gu; Shanliang Xu; Yajun Wang; Xiaojun Yan (Marine Biotechnology, 2023)

The anthropogenic effects on organic matter in sediment core based on Bayesian mixing model: a case study of Daya Bay - Xiangtian Man; Honghui Huang; Shijun Jiang; Yangguang Gu; Boguang Wang (Environmental Science and Pollution Research, 2023)

Role and mechanism of WNT5A in benzo(a)pyrene-induced acute lung injury and lung function decline - Lieyang Fan; Bin Wang; Jixuan Ma; Zi Ye; Xiuquan Nie; Man Cheng; Yujia Xie; Pei Gu; Yingdie Zhang; Xiaojie You; Yun Zhou; Weihong Chen (Journal of Hazardous Materials, 2023)

Gypenosides suppress hepatocellular carcinoma cells by blocking cholesterol biosynthesis through inhibition of MVA pathway enzyme HMGCS1 - Man-Yu Xiao; Fang-Fang Li; Peng Xie; Yan-Shuang Qi; Jin-Bo Xie; Wen-Jing Pei; Hao-Tian Luo; Mei Guo; Yu-Long Gu; Xiang-Lan Piao (Chemico-Biological Interactions, 2023)

Interface engineered Ni3Se2/Ni3S2/NF heterostructure as a highly efficient electrocatalyst for robust oxygen evolution reaction - Man Lin; Mingzheng Gu; Xueya Deng; Qiang Xie; Xiaojun Zhang (Chemical Engineering Journal, 2023)

Cardiac sapogenins from Periploca forrestii - Jun Jin; Man Meng; Jun-you Jian; Wei Gu; Chun-mao Yuan; Xiao-jiang Hao; Lie-jun Huang (Phytochemistry Letters, 2023)

Asymmetric coordinated single-atom Pd sites for high performance CO2 electroreduction and Zn–CO2 battery - Jiani Li; Li-Wei Chen; Yu-Chen Hao; Man Yuan; Jianning Lv; Anwang Dong; Shuai Li; Hongfei Gu; An-Xiang Yin; Wenxing Chen; Pengfei Li; Bo Wang (Chemical Engineering Journal, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

Recent advances in biotechnological production of polyunsaturated fatty acids by Yarrowia lipolytica - Yu-Lei Jia; Ling-Ru Wang; Zi-Xu Zhang; Yang Gu; Xiao-Man Sun (Critical Reviews in Food Science and Nutrition, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

Transcriptome Profiling of Duodenum Reveals the Importance of Boron Supplementation in Modulating Immune Activities in Rats - Chunfang Zhao; Yujiao Han; Chenfang Wang; Man Ren; Qianqian Hu; Youfang Gu; Pengfei Ye; Shenghe Li; Erhui Jin (Biological Trace Element Research, 2022)

Statistical optimization of phytol and polyunsaturated fatty acid production in the Antarctic microalga Micractinium variabile KSF0031 - Eun Jae Kim; Hyunsik Chae; Man Hyung Koo; Jihyeon Yu; Hyunjoong Kim; Sung Mi Cho; Kwang Won Hong; Joo Young Lee; Ui Joung Youn; Sanghee Kim; Han-Gu Choi; Se Jong Han (Algae, 2022)
Polar microorganisms produce physiologically active substances to adapt to harsh environments, and these substances can be used as biomedical compounds. The green microalga Micractinium variabile KSF0031, which was isolated from Antarctica, produced phytol, a natural antimicrobial agent. Furthermore, several polyunsaturated fatty acids (PUFAs), including omega-3, exhibit antioxidant properties. Here statistical methods (Plackett-Burman design and Box- Behnken design) were used to optimize the culture medium of KSF0031 to improve biomass production, and K2HPO4, MgSO4·7H2O, and ammonium ferric citrate green (AFCg) were selected as significant components of the culture medium. Changes in the concentration of K2HPO4 and MgSO4·7H2O as positive factors and AFCg as a negative factor affected cell growth to a remarkable degree. The biomass production in a 100 L culture using the optimized medium for 24 d at 18°C was improved by 37.5% compared to that obtained using the original BG-11 medium. The quantities of PUFAs and phytol obtained were 13 mg g-1 dry cell weight (DCW) and 10.98 mg g-1 DCW, which represent improved yields of 11.70% and 48.78%, respectively. The results of this study could contribute to an improved production of phytol and fatty acids from Antarctic microalgae in the biomedical industry.

Functional connectivity dynamics as a function of the fluctuation of tension during film watching - Yadi Sun; Junji Ma; Miner Huang; Yangyang Yi; Yiheng Wang; Yue Gu; Ying Lin; Liman Man Wai Li; Zhengjia Dai (Brain Imaging and Behavior, 2022)

Artificial modification of Earth’s radiation belts by ground-based very-low-frequency (VLF) transmitters - Binbin Ni; Man Hua; Xudong Gu; Song Fu; Zheng Xiang; Xing Cao; Xin Ma (Science China Earth Sciences, 2022)

Genetic diversity and structure of Oncomelania hupensis hupensis in two eco-epidemiological settings as revealed by the mitochondrial COX1 gene sequences - Jie-Ying Zhang; Man-Man Gu; Qiu-Fu Yu; Meng-Tao Sun; Hui-Ying Zou; Zhi-Jun Zhou; Da-Bing Lu (Molecular Biology Reports, 2022)

Immune response of silver pomfret ( Pampus argenteus ) to Amyloodinium ocellatum infection - Youyi Zhang; Jiabao Hu; Yaya Li; Man Zhang; Kimran Jean Jacques; Weiwei Gu; Yibo Sun; Jiachu Sun; Yang Yang; Shanliang Xu; Yajun Wang; Xiaojun Yan (Journal of Fish Diseases, 2021)
Amyloodinium ocellatum (AO) infection in silver pomfret ( Pampus argenteus ) causes extensive mortality. Insufficient information exists on the molecular immune response of silver pomfret to AO infestation, so herein we simulated the process of silver pomfret being infected by AO. Translucent trophosomes were observed on the gills of AO‐infected fish. Transcriptome profiling was performed to investigate the effects of AO infection on the gill, kidney complex and spleen. Overall, 404,412,298 clean reads were obtained, assembling into 96,341 unigenes, which were annotated against public databases. In total, 2730 differentially expressed genes were detected, and few energy‐ and immune‐related genes were further assessed using RT‐qPCR. Moreover, activities of three immune‐related (SOD, AKP and ACP) and three energy‐related (PKM, LDH and GCK) enzymes were determined. AO infection activated the immune system and increased interleukin‐1 beta and immunoglobulin M heavy chain levels. Besides, the PPAR signalling pathway was highly enriched, which played a role in improving immunity and maintaining homeostasis. AO infection also caused dyspnoea, leading to extensive lactic acid accumulation, potentially contributing towards a strong immune response in the host. Our data improved our understanding regarding the immune response mechanisms through which fish coped with parasitic infections and may help prevent high fish mortality in aquaculture.

Effect of Boron on Microstructure, Immune Function, Expression of Tight Junction Protein, Cell Proliferation and Apoptosis of Duodenum in Rats - Ting Liu; Chenfang Wang; Xiaoshuang Wu; Man Ren; Qianqian Hu; Erhui Jin; Youfang Gu (Biological Trace Element Research, 2021)

A high-density genetic map and multiple environmental tests reveal novel quantitative trait loci and candidate genes for fibre quality and yield in cotton - Qishen Gu; Huifeng Ke; Zhengwen Liu; Xing Lv; Zhengwen Sun; Man Zhang; Liting Chen; Jun Yang; Yan Zhang; Liqiang Wu; Zhikun Li; Jinhua Wu; et al. (Theoretical and Applied Genetics, 2020)

Update on recommendations for the diagnosis and treatment of SARS-CoV-2 infection in children - Hongjun Miao; Han Li; Yinying Yao; Mingfu Wu; Chao Lu; Jun Wang; Man Tian; Ying Li; Peiliang Luo; Jianhui Gu; Bin Yuan; Shouchuan Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
Since the outbreak of novel coronavirus infection pneumonia in Wuhan City, China, in late 2019, such cases have been gradually reported in other parts of China and abroad. Children have become susceptible to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) because of their immature immune function. As the outbreak has progressed, more cases of novel coronavirus infection/pneumonia in children have been reported. Compared with adults, the impact of SARS-CoV-2 infection in children is less severe, with a lower incidence and susceptibility in children, which results in fewer children being tested, thereby underestimating the actual number of infections. Therefore, strengthening the diagnosis of the disease is particularly important for children, and early and clear diagnosis can determine treatment strategies and reduce the harm caused by the disease to children. According to the Novel Coronavirus Infection Pneumonia Diagnosis and Treatment Standards ( trial version 7 ) issued by National Health Committee and the latest diagnosis and treatment strategies for novel coronavirus infection pneumonia in children, this review summarizes current strategies on diagnosis and treatment of SARS-CoV-2 infection in children.

Trophic Ecology and Ecological Function for Oriental River Prawn (Macrobrachium nipponense) in the South-to-North Canal System - Man Zhang; Nan Li; Binhe Gu; Yuncong Li; Yifan Wang; Wenguang Dong; Yunni Gao; Chuanjiang Zhou; Guoxing Nie (Wetlands, 2020)

The characteristics and genome analysis of vB_ApiP_XC38, a novel phage infecting Acinetobacter pittii - Mengjun Cheng; Man Luo; Hengyu Xi; Yunze Zhao; Shuai Le; Li-Kuang Chen; Demeng Tan; Yuan Guan; Tianqi Wang; Wenyu Han; Nannan Wu; Tongyu Zhu; et al. (Virus Genes, 2020)

Enhanced pyrogallol toxicity to cyanobacterium Microcystis aeruginosa with increasing alkalinity - Yunni Gao; Qinqin Fu; Jing Lu; Hui Yang; Philip T. Orr; Fang Zhang; Jing Dong; Man Zhang; Qianhong Gu; Chuanjiang Zhou; Michele A. Burford (Journal of Applied Phycology, 2020)

Spatial distribution and filtering efficiency of Daphnia in a deep subtropical reservoir - Man Zhang; Rebecca Ashley Smyth; Weixia Zhu; Li Zhang; Yuncong Li; Yifan Wang; Xuejun Li; Qianhong Gu; Yunni Gao (Journal of Oceanology and Limnology, 2019)

Effect of silicon in Pyropia yezoensis under temperature and irradiance stresses through antioxidant gene expression - Bao Le; Mawra Nadeem; Seung-Hwan Yang; Jong-Am Shin; Man-Gu Kang; Gyuhwa Chung; Sangmi Sun (Journal of Applied Phycology, 2019)

Enhanced growth rate and ulvan yield of Ulva pertusa using light-emitting diodes (LEDs) - Bao Le; Jong-Am Shin; Man-Gu Kang; Sangmi Sun; Seung Hwan Yang; Gyuhwa Chung (Aquaculture International, 2018)

Integrated analysis of transcriptomic and metabolomic data reveals critical metabolic pathways involved in rotenoid biosynthesis in the medicinal plant Mirabilis himalaica - Li Gu; Zhong-yi Zhang; Hong Quan; Ming-jie Li; Fang-yu Zhao; Yuan-jiang Xu; Jiang Liu; Man Sai; Wei-lie Zheng; Xiao-zhong Lan (Molecular Genetics and Genomics, 2018)

Links between Western Pacific Subtropical High and vegetation growth in China - Mei Huang; Man Hao; Shaoqiang Wang; Li Dan; Fengxue Gu; Zhaosheng Wang; He Gong (Journal of Geographical Sciences, 2018)

Enrichment and In Vitro Culture of Spermatogonial Stem Cells from Pre-Pubertal Monkey Testes - Yong-Hee Kim; Hyun-Gu Kang; Bang-Jin Kim; Sang-Eun Jung; Polash C. Karmakar; Seok-Man Kim; Seongsoo Hwang; Buom-Yong Ryu (Tissue Engineering and Regenerative Medicine, 2017)

Boron Affects Immune Function Through Modulation of Splenic T Lymphocyte Subsets, Cytokine Secretion, and Lymphocyte Proliferation and Apoptosis in Rats - Erhui Jin; Shenghe Li; Man Ren; Qianqian Hu; Youfang Gu; Kui Li (Biological Trace Element Research, 2017)

Profiling the biological effects of wastewater samples via bioluminescent bacterial biosensors combined with estrogenic assays - Ingrid Bazin; Ho Bin Seo; Carey M. Suehs; Marc Ramuz; Michel De Waard; Man Bock Gu (Environmental Science and Pollution Research, 2017)

Analysis of genetic diversity and population structure of Bellamya quadrata from lakes of middle and lower Yangtze River - Qianhong Gu; Man Zhang; Chuanjiang Zhou; Guorong Zhu; Jing Dong; Yunni Gao; Jie Chen; Peng Chen (Genetica, 2015)

The Regenerating Spinal Cord of Gecko Maintains Unaltered Expression of β-Catenin Following Tail Amputation - Honghua Song; Lili Man; Yingjie Wang; Xue Bai; Sumei Wei; Yan Liu; Mei Liu; Xiaosong Gu; Yongjun Wang (Journal of Molecular Neuroscience, 2015)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Roles of Wnt/β-Catenin Signaling in Retinal Neuron-Like Differentiation of Bone Marrow Mesenchymal Stem Cells from Nonobese Diabetic Mice - Yue Xu; Zhifeng Gu; Biyu Shen; Guofeng Xu; Tianqiu Zhou; Jinxia Jiang; Jing Xing; Suzhe Liu; Man Li; Wei Tan; Guijuan Feng; Aimin Sang; et al. (Journal of Molecular Neuroscience, 2013)

RNAi-directed down-regulation of RSV results in increased resistance in rice (Oryza sativa L.) - Yong Zhou; Yuan Yuan; Fuhai Yuan; Man Wang; Huan Zhong; Minghong Gu; Guohua Liang (Biotechnology Letters, 2012)

A linkage map of cultivated cucumber (Cucumis sativus L.) with 248 microsatellite marker loci and seven genes for horticulturally important traits - Han Miao; Shengping Zhang; Xiaowu Wang; Zhonghua Zhang; Man Li; Shengqi Mu; Zhouchao Cheng; Ruowei Zhang; Sanwen Huang; Bingyan Xie; Zhiyuan Fang; Zhenxian Zhang; et al. (Euphytica, 2011)

Fine mapping and candidate gene analysis of ptgms2-1, the photoperiod-thermo-sensitive genic male sterile gene in rice (Oryza sativa L.) - Jianjun Xu; Baohe Wang; Yinhui Wu; Peina Du; Jun Wang; Man Wang; Chuandeng Yi; Minghong Gu; Guohua Liang (Theoretical and Applied Genetics, 2011)

A Multi-Channel Continuous Water Toxicity Monitoring System: Its Evaluation and Application to Water Discharged from a Power Plant - Byoung Chan Kim; Man Bock Gu (Environmental Monitoring and Assessment, 2005)

Biodegradation of dipropyl phthalate and toxicity of its degradation products: a comparison of Fusarium oxysporum f. sp. pisi cutinase and Candida cylindracea esterase - Yang-Hoon Kim; Jiho Min; Kyung-Dong Bae; Man Bock Gu; Jeewon Lee (Archives of Microbiology, 2005)

Physicochemical Factors Affecting the Sensitivity of Ceriodaphnia dubia to Copper - Sang Don Kim; Man Bock Gu; Herbert E. Allen; Daniel K. Cha (Environmental Monitoring and Assessment, 2001)

Preface - Man Bock Gu; Young Joon Kim (Environmental Monitoring and Assessment, 2001)

The Continuous Monitoring of Field Water Samples with a Novel Multi-Channel Two-Stage Mini-Bioreactor System - Man Bock Gu; Byoung Chan Kim; Jaeweon Cho; Peter D. Hansen (Environmental Monitoring and Assessment, 2001)

Carcinogenic potential and genomic instability of beryllium sulphate in BALB/c‐3T3 cells - Nagalakshmi Keshava; Gu Zhou; Michelle Spruill; Mang Ensell; Tong-man Ong (Molecular and Cellular Biochemistry, 2001)

Plant regeneration from callus cultures ofLithospermum erythrorhizon - Hee-Ju Yu; Soo Kyung Oh; Man-Ho Oh; Dong-Woog Choi; Young Myung Kwon; Sang-Gu Kim (Plant Cell Reports, 1997)

Plant regeneration from callus cultures of Lithospermum erythrorhizon - Hee-Ju Yu; Soo Kyung Oh; Man-Ho Oh; Dong-Woog Choi; Young Myung Kwon; Sang-Gu Kim (Plant Cell Reports, 1997)